Kewarganegaraan Sebagai Hak Konstitusional: Penegak Hak Sipil dan Politik di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Hanifah Muslimah; Rana Inas Zahira; Dina Setiana Pratiwi (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This study examines citizenship as a constitutional right in Indonesia, focusing on the foundational principles of citizenship, the roles of state institutions, challenges in the enforcement of rights, and relevant case studies. The research employs a doctrinal legal methodology with a normative approach, incorporating legislative, case law, conceptual, historical, and comparative perspectives. Data is collected from primary, secondary, and tertiary legal sources through a literature review. The analysis reveals that the foundational principles of citizenship are enshrined in the 1945 Constitution of Indonesia (UUD 1945), which includes the right to participate in government, the right to decent work, and other social rights. State institutions such as the President, the People's Consultative Assembly (DPR), and the judiciary play crucial roles in the enforcement of constitutional rights. However, several challenges persist, including human rights violations, injustices within the legal system, and barriers to political participation. Case studies related to administrative issues in the 2024 elections, human rights violations in Papua, and the controversy surrounding the Omnibus Law on Job Creation illustrate practical issues in the implementation of constitutional rights.